Predictors of home discharge among patients hospitalized for behavioural and psychological symptoms of dementia. Issue 4 (27th April 2015) - Tochimoto, Shinnichi; Kitamura, Maki; Hino, Shoryoku; Kitamura, Tatsuru
Abstract: Background: The Japanese government recently announced the 'Five‐Year Plan for Promotion of Measures Against Dementia (Orange Plan)' to promote people with dementia living in their communities. To achieve this, it is imperative that patients hospitalized with behavioural and psychological symptoms of dementia (BPSD) are helped to return to their own homes. The aim of the present study was to identify predictors of home discharge among patients hospitalized for BPSD. Methods: A single‐centre chart review study was conducted on consecutive patients hospitalized from home between April 2006 and March 2011 for the treatment of BPSD. The frequency of discharge back to home was examined in relation to a patient's active behavioural problems and demographics at the time of admission. Diagnoses of dementia were made on the basis of the Diagnostic and Statistical Manual of Mental Disorders, 4th edition, and consensus guidelines for the clinical and pathologic diagnosis of dementia with Lewy bodies. Results: In all, 391 patients were enrolled in the study. Of these patients, 163 (42%) returned home. Multiple logistic regression analysis identified high Mini‐Mental State Examination and Nishimura‐style senile activities of daily living scores as significant independent predictors of home discharge. In contrast, living alone and manifestation of aggressiveness at the time of admission were negatively associated with home discharge. Conclusions: Few patients hospitalized for BPSD are discharged home, and this number is affected by a patient's clinical and demographic characteristics at the time of admission. These findings should be considered in designing and implementing optimal management and care strategies for patients with BPSD.